Estrogen–progestin replacement therapy: regulatory action needed - Pike, Malcolm C (BioMed Central, 2002)
It is now established that the most commonly prescribed estrogen–progestin replacement therapy regimen significantly increases breast cancer risk. What are the risks associated with other regimens? Studies with breast cancer as the outcome cannot answer these questions in the right timeframe. It is incumbent on us to agree that some intermediate marker of risk must be used to show the probable effect of a regimen. We should then act as if the effect on the marker is a quantitative guide to the probable effect on breast cancer risk. Regulatory authorities need to require such studies on all current regimens.